Development and evaluation of Chrysin-Phospholipid complex loaded solid lipid nanoparticles - storage stability and in vitro anti-cancer activity. (18th August 2018) - Komath, Shahadali; Garg, Anuj; Wahajuddin, Muhammad
Abstract: Context: Flavonoids show promising anticancer potential but it is limited due to poor solubility. Objective: The present investigation was to prepare Chrysin-Phospholipid complex loaded solid lipid nanoparticles (Ch-PC-SLNs) for improving its encapsulation as compared to that of Chrysin loaded SLNs (Ch-SLNs) and evaluated for potential increase in the anti-cancer activity against MCF-7 cell line. Methods: The physiochemical characteristics and release kinetics for Ch-SLNs and Ch-PC-SLNs were evaluated and compared. Storage stability of Ch-PC-SLNs was evaluated up to 3 months. Solid state properties (DSC, XRD) and morphology (AFM) of Ch-PC-SLNs were also studied. In-vitro anticancer activity was investigated by using MTT assay. Results and Discussion: Ch-PC-SLNs exhibited higher encapsulation efficiency than Ch-SLNs and zero order release kinetics. Ch-PC-SLNs were found to be stable upto 3 months upon lyophilisation with mannitol as cryoprotectant. DSC and XRD study revealed the loss of highly crystalline nature of Chrysin in Ch-PC-SLNs. The Ch-PC-SLNs lead to significantly higher in-vitro anticancer activity than that of bulk Chrysin. Conclusion: The study concludes that phospholipids complex with Chrysin lead to improve encapsulation, storage stability of SLNs and in vitro anticancer activity.